(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the concept of almost strongly θ(Λ, p)-continuous functions. Moreover, some characterizations of almost strongly θ(Λ, p)-continuous functions are considered.